Impact of early childhood trauma on retention and phase advancement in an outpatient buprenorphine treatment program. Issue 7 (15th September 2016) - Kumar, Nihit; Stowe, Zachary N.; Han, Xiaotong; Mancino, Michael J.
Abstract : Background: Early adverse life events such as childhood trauma have been linked to development of substance use disorders. The prevalence and impact on treatment of early childhood trauma in opioid‐dependent individuals has received limited research attention. The present study examined reported childhood trauma and its relation to retention and adherence in an outpatient buprenorphine treatment program. Methods: Medical records of individuals who completed childhood trauma questionnaire (CTQ) were reviewed to extract baseline data and demographics ( N = 113). Total and subscale CTQ scores were dichotomized to low versus moderate‐severe levels of trauma. Treatment course evaluation was based on successful phase advancement and retention in treatment during the first 90 days. Logistic regression models were used to examine associations between CTQ subscales and total score and the two outcomes adjusting for covariates. Results: Moderate‐severe trauma defined by total CTQ score was present in 16% of participants. Logistic regression models showed significant associations between physical and emotional neglect and drop out after adjusting for covariates. Individuals who had never married and those with positive admission urine drug screen for opiates associated significantly with drop out. Conclusions and Scientific Significance: The results from a convenience sample participating in a university‐based buprenorphine treatment program demonstrated significant association between self‐reported early childhood trauma and retention during the first 90 days. These findings suggest that addressing early trauma could potentially improve adherence rates leading to reduced disease burden. This study extends the knowledge base on potential predictive factors associated with successful participation in outpatient buprenorphine treatment. (Am J Addict 2016;25:542–548)